Škoda od parkljaste divjadi v kmetijskem prostoru na območju Gojitvenega lovišča Kompas - Peskovci na Goričkem - Gönter, Peter (Gozdarski vestnik, 2007)
The article examines some of the factors which trigger off and influence the development and scope of damage caused by red deer and wild boar in the agricultural area of the wildlife reserve Kompas-Peskovci in the region Goričko, covering a total of 13,000 ha. It states the reasons and direct causes for damage, as well as the interdependence between the damage size and the population density, climatic conditions and harvest size. By linear and multiple regression analysis and by calculating correlations the relations between the damage and individual variables are determined.
Keywords: divjad; jelenjad; divji prašič; Skoda; škoda; kmetijski pridelki; Goričko; Slovenia; Slovenija